INTERNATIONAL LEGAL COOPERATION AND THE PRINCIPLE OF EQUALITY AMONG NATIONS: LESSONS FROM CRIMINAL LAW AND PROCEDURE - DOI 10.5935/2448-0517.20200027 - Griffin, Lissa (Juris Poiesis - Qualis A3, 2020)
International efforts to achieve fair, efficient and reliable criminal justice systems can benefit from the openminded exchange of ideas, values, and choices among nations, each respecting the other"s contributions. Obstacles exist to the United States" fully joining this effort in its insistence on American exceptionalism and its continued reliance on unreliable evidence.